A virtual safe space? An approach of intersectionality and social identity to behavior in virtual environments - Szita, Kata (My University, 2022)
Health measures in response to the Covid-19 pandemic have confined millions to their homes and minimized social contacts. During this period, a significant proportion of social activities—including work, education, and recreation—moved to digital media platforms. Among these platforms, social virtual reality (VR) has gained importance offering “alternative” realities in which users can engage with others, participate in cultural and sports events, complete education-related activities, and (mental) health treatments, to name but a few functions. With the increasing popularity of social VR and the expanding range of activities these platforms can host, hitherto-unexplored questions arise regarding social interactions and the representation of virtual bodies. Therefore, the objective of this paper is to outline a potential framework for assessing how avatars that represent various body types and demographic characteristics, such as gender or ethnicity, may impact behaviors and identity. The paper presents a theoretical study that combines social identity theory and theories of intersectionality and applies them to the case of digitally created human-like bodies. By doing this, it illuminates the challenges and benefits virtual reality platforms and digital body representations hold—including remote social interactions due to social isolation and social dynamics based on online personas.
PUBLISHED
Keywords: Social virtual reality; Intersectionality; Social identity; Virtual body; Avatars; Creative Arts Practice; Creative Technologies; Digital Engagement; Inclusive Society; Telecommunications; Embodiment; Extended Reality; Intersectionality; Social Identity; Virtual Reality; avatars; social virtual reality; Community; Communication; Culture; Gender; Social exclusion